Interdomain and Intermodule Organization in Epimerization Domain Containing Nonribosomal Peptide Synthetases - Chen, Wei-Hung; Li, Kunhua; Guntaka, Naga Sandhya; Bruner, Steven D (ACS chemical biology, 2016)
Nonribosomal peptide synthetases are large, complex multidomain enzymes responsible for the biosynthesis of a wide range of peptidic natural products. Inherent to synthetase chemistry is the thioester templated mechanism that relies on protein/protein interactions and interdomain dynamics. Several questions related to structure and mechanism remain to be addressed, including the incorporation of accessory domains and intermodule interactions. The inclusion of nonproteinogenic d-amino acids into peptide frameworks is a common and important modification for bioactive nonribosomal peptides. Epimerization domains, embedded in nonribosomal peptide synthetases assembly lines, catalyze the l- to d-amino acid conversion. Here we report the structure of the epimerization domain/peptidyl carrier protein didomain construct from the first module of the cyclic peptide antibiotic gramicidin synthetase. Both holo (phosphopantethiene post-translationally modified) and apo structures were determined, each representing catalytically relevant conformations of the two domains. The structures provide insight into domain–domain recognition, substrate delivery during the assembly line process, in addition to the structural organization of homologous condensation domains, canonical players in all synthetase modules.